علوم الحديث في مقدمات وخواتيم كتب السنة - قعري, حيدر; بن عثمان, نجيب (University Of Eloud جامعة الوادي, 2019)
"تعد كتب السنة مصدرا للحديث وعلومه، وذلك أن أصحاب هذه الكتب وضعوا قواعد يميزون بها الصحيح من السقيم، في ترتيب كتبهم أو مقدمات وخواتيم كتبهم، ولهذا احتفت مقدمات وخواتيم الائمة بعلوم مختلفة من علوم الحديث. ولهذا كان الموضوع تحت عنوان ""علوم الحديث في مقدمات وخواتيم كتب السنة"". ثم تكلمنا على هذا الم وضوع، فقمنا بدراسة علوم الحديث في مقدمات وخواتيم الصحاح، ومقدمات وخواتيم السنن، وبعد الدراسة عثرنا على تسعة مصطلحات. حيث تعد مقدمة صحيح مسلم مقدمة زاخرة بعلوم الحديث فتكلم عن الحديث المرسل والمنكر والغريب والمدلس والمعنعن والموضوع، وتكلم ابن حبان في مقدمة صحيحه عن المدلس والمرفوع، وتكلم ابو داود في رسالته الى أهل مكة عن المرسل والمتروك ا ولمنكر والمدلس والغريب، وذكر الترمذي في خاتمة العلل الصغير المرسل والحسن والغريب، وهذه الخاتمة الوحيدة التي حوت على علم المصطلح. هذا حتى نكون على علم بهذه المقدمات والخواتيم ومؤلفيها." "The books of the Sunnah are a source of Hadith and its sciences. The authors of these books set rules that distinguish the correct ones from the bad in the order of their books or the preamble and the end of their books And CONCLUSIONS of the imams with different sciences of Hadith's sciences. Therefore, the topic was entitled ""Science of Hadith in the introduction and "".finalization of the books of the Sunnah. Then we talked about this subject, so we studied the science of Hadith in the introduction and finalization of the Sahih, and the introduction and the conclusion of the Sunan, and after the study, .we found nine terms Where the preface OFMuslim introduction filled with the science of HADITA AND HE talk about the conversation sent And alienated and ignorant and disobedient and subject, and Ibn Hibban spoke in the introduction to his truth about the Almmls and Marvoua, Abu Dawood spoke in his letter to the people of Mecca about the sender, the deceased, the evil, the profane and the strange, Al-Tirmidhi mentioned in the conclusion of the small, good, strange, and strange ills, and this is the only conclusion that has become known to the term. So that we are aware of these introductions and the finalists and authors."
مذكرة ماستر تخصص الحديث وعلومه
Keywords: علوم الحديث-الخواتم-الحديث المرسل-الحديث المدلس; Hadith Sciences - The Rings - The Hadith - The Messenger - Hadith Al-Mudallos